2020
DOI: 10.1186/s12943-020-01259-6
|View full text |Cite
|
Sign up to set email alerts
|

Circular HER2 RNA positive triple negative breast cancer is sensitive to Pertuzumab

Abstract: Background Triple negative breast cancer (TNBC) remains the most challenging breast cancer subtype so far. Specific therapeutic approaches have rarely achieved clinical improvements in treatment of TNBC patients and effective molecular biomarkers are largely unknown. Methods We used paired TNBC samples and high throughput RNA sequencing to identify differentially expressed circRNAs. Sucrose gradient polysome fractionation assay, anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
98
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 42 publications
0
98
0
Order By: Relevance
“…More recently, Li et al confirmed that a newly identified HER2 transcriptional variant, circHER2 , had an open reading frame driven by an IRES and could generate a 103 amino acid protein HER2–103. HER2–103 could promote homo/hetero dimerization of epidermal growth factor receptor (EGFR)/HER3 and sustain AKT phosphorylation and downstream malignant phenotype [ 75 ]. Whith the increasing evidence prove that circRNAs could translate proteins directly [ 72 , 73 , 76 , 77 ], the notion of circRNAs are non-coding RNAs is becoming doubtful.…”
Section: Regulatory Mechanisms Of Circrnas In Tnbcmentioning
confidence: 99%
See 4 more Smart Citations
“…More recently, Li et al confirmed that a newly identified HER2 transcriptional variant, circHER2 , had an open reading frame driven by an IRES and could generate a 103 amino acid protein HER2–103. HER2–103 could promote homo/hetero dimerization of epidermal growth factor receptor (EGFR)/HER3 and sustain AKT phosphorylation and downstream malignant phenotype [ 75 ]. Whith the increasing evidence prove that circRNAs could translate proteins directly [ 72 , 73 , 76 , 77 ], the notion of circRNAs are non-coding RNAs is becoming doubtful.…”
Section: Regulatory Mechanisms Of Circrnas In Tnbcmentioning
confidence: 99%
“…Specifically, circRPPH1 , circSEPT9 , circGNB1 , circPGAP3 , circUBE2D2 , circRAD18 , circAGFG1 , circKIF4A , circPLK1 , circUBAP2 , circEPSTI1 , and circGFRA1 were upregulated in both TNBC cells and tissues, and high expression of these circRNAs was able to promote tumor cell proliferation both in vitro and in vivo, and was associated with larger tumor sizes and shorter survival times for TNBC patients [ 29 , 46 , 49 , 51 , 53 , 54 , 57 , 59 , 60 , 63 , 64 , 78 ]. Similarly, circZEB1 , circEIF3M , circHER2 , hsa_circ_0131242 , hsa_circ_0005320 , hsa_circ_069718 , hsa_circ_0058514 , and circTFCP2L1 were overexpressed in TNBC cells and tissues, and they appeared to promote cell proliferation and tumor growth of TNBC [ 55 , 58 , 62 , 75 , 79 – 82 ]. On the contrary, a few circRNAs were identified to have tumor-suppressive effects in TNBC.…”
Section: Role Of Circrnas On the Biological Functions Of Tnbcmentioning
confidence: 99%
See 3 more Smart Citations